Regulation (EU) 2021/2282 of the European Parliament and of the Council - de Farmacoterapia, Revista Portuguesa (2022)
On december 22nd, 2021, Regulation (EU) 2021/2282 of the European Parliament and of the Council on health technology assessment was published, with the goal of promoting proper functioning of the internal market with regard to medicines, medical devices and in vitro diagnostic medical devices. This regulation shall apply from January 12, 2025. A summary of the document is presented, which can be consulted at: https://eur-lex.europa.eu/legal-content/PT/TXT/?uri=CELEX:32021R2282.